Understanding the Emergence of Private Security Companies & Variance in Security Contracting - Morrison, Melissa (Université d'Ottawa | University of Ottawa, 2015)
This Major Research Paper seeks to provide a comprehensive understanding of the emergence and utilization of the private security industry. Rather than merely providing a detailed account of the multifaceted origins of the private security industry, a topic heavily debated throughout recent security literature, this paper seeks to take one step further, by tacking the puzzle of differing military contracting practices between states. Thus, the purpose of this paper is two-fold. First, to provide a detailed account of the factors that converged to create a massive industry for private security, and second, to understand why there is such variance in military contracting. Through a theoretical analysis of the existing literature, this paper argues that there is no single explanation that sufficiently justifies the significant differences in interstate contracting trends. Thus, this paper suggests that a holistic approach is necessary, where two differing explanations – a political instrumentalist explanation and a norm and idea explanation – are taken as complementary rather than competing. Using a synthetic lens, this paper demonstrates that these two disconnected factors, when taken together, are relevant for analyzing and understanding variance in military contracting.